Agensi Siswa dalam Project-Based Learning: Analisis Motivasi dan Partisipasi Siswa SMPN 7 Pematangsiantar - Gerardus Rizki Lumbangaol; Aulia Monica Tambunan; Elfia Fitrika Damanik; Isabel Selmiola Sabrina; Shesilia Regina Manik; Tia Artika Muliani Manurung; Marlina Sinaga; Jonathan Halomoan Sinaga; Marlina Agkris Tambunan (Young Journal of Social Sciences and Humanities, 2026)
This study aims to analyze student agency through the manifestation of motivation and participation within the Project-Based Learning (PjBL) model at SMP Negeri 7 Pematangsiantar. Employing a descriptive qualitative approach, this research explores how students articulate their self-capacity within a project-based learning ecosystem. Data were collected through observation, interviews, and documentation involving the students. The data analysis is grounded in the dimensions of intrinsic-extrinsic motivation as well as cognitive, emotional, and social participation. The results indicate that PjBL serves as an incubation space for agency, capable of enhancing students' intrinsic motivation and learning autonomy. However, the findings reveal that student agency is not uniform; variations in engagement arise due to the influence of self-efficacy and the dynamics of peer relations within groups. These findings underscore that student agency develops optimally when supported by adaptive teacher facilitation, authentic project relevance, and inclusive group management. This study concludes that PjBL effectively acts as a catalyst for student agency when implemented contextually in learning situations that value student voice and choice.